Study of melissopalynological, physical and chemical properties, antioxidant and xanthine oxidase inhibition activity of heterotrigona itama honey in Johor, Malaysia - Majid, Mahani (2019)
Stingless bee honey or known as ‘madu kelulut’ by Malaysian native started to receive attention due to their acclaimed medicinal values and health benefits. To date, there are limited reports of stingless bee honey compositions available in Malaysia. Therefore, the objective of this study was to identify the plant sources, physical and chemical properties, antioxidant and xanthine oxidase inhibition activity of Heterotrigona itama honey from six selected area in Johor, Malaysia. Plant sources of honey were identified by melissopalynological analysis, and multiply methods were conducted to investigate the physical and chemical properties of honey. Three different antioxidant assays (DPPH scavenging, ABTS decolourization and FRAP), together with phenolic compounds, total phenolic and flavonoid content were also evaluated. Then, enzyme activity was tested by xanthine oxidase inhibition assay. The pollen identification of honeys has clustered them into unifloral and multifloral honey where Cocos nucifera and Rhizophora mucronata species were identified as predominant pollen types. All analyzed honey samples meet the national standard requirements (electrical conductivity: 0.57 mS/cm; pH value: 3.40, colour intensity: 692 mAU, moisture content: 28.95 g/100g, ash content: 0.37 g/100g, sugar content: 20.25 g/100g) which showed them as a good quality product. HPLC screening detected six phenolic acids (chlorogenic acid, epicatechin, P-Coumaric acid, rutin, catechin and protocatheuic) which present in various combination. Unifloral honey (R. mucronata) possessed the highest phenolic (413.94 mg GAE/100g) and flavonoid (179.36 mg RE/100g) content and have the highest antioxidant (DPPH: 74.03 %; ABTS: 65.02 %; FRAP: 1401.80 uM Fe(II)/100g) and enzyme inhibition (IC50: 30.0 mg/mL) activity. This study highlights the importance of plant sources of honey which may increase its commercial value and could be significant contribution to the database for the sustainability of stingless bee industry in Malaysia.